Non-destructive electron microscopy imaging and analysis of biological samples with graphene coating. (28th September 2016) - Park, Jong Bo; Kim, Yong-Jin; Kim, Seong-Min; Yoo, Je Min; Kim, Youngsoo; Gorbachev, Roman; Barbolina, I I; Kim, Sang Jin; Kang, Sangmin; Yoon, Myung-Han; Cho, Sung-Pyo; Novoselov, Konstantin S; et al.
Abstract: In electron microscopy (EM), charging of non-conductive biological samples by focused electron beams hinders their high-resolution imaging. Gold or platinum coatings have been commonly used to prevent such sample charging, but it disables further quantitative and qualitative chemical analyses such as energy dispersive spectroscopy (EDS). Here we report that graphene-coating on biological samples enables non-destructive high-resolution imaging by EM as well as chemical analysis by EDS, utilizing graphene's transparency to electron beams, high conductivity, outstanding mechanical strength and flexibility. We believe that the graphene-coated imaging and analysis would provide us a new opportunity to explore various biological phenomena unseen before due to the limitation in sample preparation and image resolution, which will broaden our understanding on the life mechanism of various living organisms.